Daughterly Narratives in Search of Voice: Fadwa Tuqan, Latifa al-Zayyat, and Samar Attar - Bedeir, Rania (AUC Knowledge Fountain, 2023)
A myriad of pressures and struggles affect Arab women as they are coming of age due to the familial and societal constructs they face. As daughters, they yearn for a voice amidst a plethora of generational boundaries, transmissions, and ideals. The intricacy of the psychological and interconnected structural factors is augmented by their gender in societies that are motivated, and often governed by, the implications of gender roles. While multiple layers of influence such as familial and sociocultural institutions affect how consciousness is formed, generational transmission, through the maternal figure, is paramount. Daughters, therefore, cannot narrate their personal stories without including the influence of the mother or the maternal figure. Mothers pass on the social definitions of their daughters’ expected role as a woman, which have paramount effects on the daughters’ development and process of individuation. Through close reading, this research aims to explore and analyze the tripartite structure that dominates their daughterly narratives. Firstly, it will explore the effects of mother-daughter relationships within the familial and socio-cultural context, which have a pronounced impact on the heroines’ journeys of subject formation. Secondly, it will analyze the interplay between the individual and the collective and its impact on the heroines’ motivations and subsequent courses of action. Finally, the research will study the heroines’ journeys as they go beyond the norm to break the generational cycles and carve out their own path to autonomy and liberation, essentially, their own voice.